The role of HR specialists in fostering innovation: an empirical study on Bangladeshi firms - Hasan, Monzurul (2022)
Enterprises are fundamentally shifting with new business models to adapt to the new realities of business rapidly. Over the past decades, researchers and entrepreneurs have constantly debated the role of HR’s contribution to creating an innovative workforce to allow the organizations to meet future needs. While most scholars conducted their research in developed countries, there is rarely any empirical evidence in HR’s role to foster innovation in Bangladeshi employees.